Business acceleration and incubation help African agripreneurs access markets - Sudarkasa, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
Michael Sudarkasa, CEO of Africa Business Group, shares some challenges in regards to youth engagement in agriculture and proposes acceleration and incubation as one solution for access to market.